Antiretroviral activity of Amazonian plants - Mata, Élida Cleyse Gomes da (2011)
The Amazon region displays a rich and diverse biota encompassing more than 50,000 botanical species. A few medicinal plants commonly utilized by local people has been studied concerning its pharmacological properties. New antiretroviral drugs are on demand, mainly in developing countries and particularly in Brazil, which exhibit an exuberant biota, it is mandatory to rationally explore its immense and diverse floristic potential for medicinal purposes.